TMEM115: a promising marker for glioma immunotherapy and prognosis - Yin, Hang; Wang, Feng; Xu, Haiyan; Xu, Manyu; Lu, Pengpeng; Zhang, Xiaojing; Yang, Lei; Lu, Bing; Sun, Pingping; Huang, Jianfei (Frontiers in Immunology, 2025)
BackgroundGlioma is a common malignant primary brain tumor characterized by a highly immunosuppressive tumor microenvironment and unfavorable prognosis. Transmembrane protein 115 (TMEM115) is a protein-coding gene. It may play a role in the retrograde transport of proteins from the Golgi to the endoplasmic reticulum. At the same time, it may also play an indirect role in protein glycosylation at the Golgi. However, the role of TMEM115 in glioma progression is still unclear and, therefore, needs further exploration.MethodsRNA-seq data from The Cancer Genome Atlas and Chinese Glioma Genome Atlas databases of glioma patients and multiplex Immunohistochemistry by glioma tissue microarrays were analyzed to determine the expression and localization of TMEM115. Functional assessment of TMEM115 involved cell proliferation, migration, and invasion assays. Pearson’s test was utilized to evaluate the association between TMEM115 protein levels, tumor immune infiltrating cells, and immune checkpoints. In addition, χ2 test and Cox regression analyses were performed to investigate whether TMEM115 protein expression is related to clinical characteristics and patient outcomes.ResultsThe results revealed a significant increase in TMEM115 expression in tumors than in non-tumor brain tissues, and knockdown of TMEM115 affects the ability of glioma cell lines to proliferate, migrate, and invade. Additionally, a significant correlation between TMEM115 protein, M2 macrophages (CD68+CD163+), and programmed cell death ligand-1 (PD-L1). Further analysis confirmed a correlation between TMEM115 protein expression in glioma tissues, World Health Organization Grade, and patients’ poorer prognosis.ConclusionThese findings support TMEM115 as a potential independent prognostic biomarker in glioma and suggest its promise as a target for immunotherapy.